Unique relations between post-traumatic stress disorder symptoms and patient functioning in type 2 diabetes. (April 2020) - Arigo, Danielle; Juth, Vanessa; Trief, Paula; Wallston, Kenneth; Ulbrecht, Jan; Smyth, Joshua M
This study examined reported post-traumatic stress disorder symptoms in adults with poorly controlled type 2 diabetes who had no history of psychiatric diagnosis or treatment ( n  = 184, MHbA1c  = 9.13%, standard deviation = 1.68). Participants reported moderate to severe intensity of post-traumatic stress disorder symptoms ( M  = 19.17, SD = 17.58). Together, depressive and post-traumatic stress disorder symptoms accounted for 10–40 percent of the variance in type 2 diabetes outcomes; post-traumatic stress disorder symptoms were associated with elevated diabetes distress and more frequent exercise and self-blood glucose testing (unique R 2  ~ 3%). Post-traumatic stress disorder symptoms may be overlooked in type 2 diabetes among patients without formal psychiatric diagnoses, and warrant increased attention.